Novel topological phases in exciton-polariton - Bao, Ruiqi (Nanyang Technological University, 2025)
An exciton-polariton is a kind of quasi particle formed when an exciton and a photon are in the strong coupling regime. It inherits properties from both the photon and exciton: small effective mass (in a microcavity), finite lifetime, strong nonlinearity, reaction to external magnetic and electrical fields, etc. These properties make microcavities containing exciton-polaritons a suitable platform to investigate novel topological phases. This thesis concerns four different theoretical proposals regarding novel topological phases in exciton-polariton systems. First, I demonstrate a way to realize antichiral edge states in a honeycomb exciton-polariton lattice. The staggered arrangement of magnetic field on two sublattices shifts the energy of Dirac points differently and results in antichiral edge states which provide robust spin propagation along the edge. Next, I introduce a method to achieve an enhanced spatial coherence by using an effect called non-Hermitian morphing, which describes how the spatial distribution of a defect mode can be drastically changed by the non-Hermitian skin effect. The enhanced coherence length is much larger than that of a (topologically) trivial system, which is useful in making polaritonic devices. In the following, I extend the non-Hermitian skin effect into a two dimensional system and achieve non-Hermitian corner modes where all the eigenstates are localized at the corners. I find that the two dimensional system provides more freedom and polaritons can propagate around point and line defects. By calculating the spectrum of fluctuations, I show that the non-Hermitian corner modes are still present in the nonlinear regime. At last, I propose to couple the non-Hermitian skin effect and the antichiral edge states and find the so called hybrid skin-topological states. Due to the non-Hermitian skin effect, the antichiral edge states are re-localized at the corners and remain spin-polarized. The hybrid skin-topological states provide robust spin propagation, which is important for spin-dependent devices.